Analisis Implementasi Rantai Pasokan Halal di Almaz Fried Chicken Cabang Condet - Rachmat Darmawan (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
This study aims to analyze the implementation of the Halal Supply Chain (HSC) at Almaaz Fried Chicken Outlet Condet Branch and its conformity with the Halal Product Assurance System (SJPH) criteria established by the Halal Product Assurance Organizing Agency (BPJPH). The research uses a qualitative method with data collected through in-depth interviews with the Outlet Manager. The interview results were compared with BPJPH regulations, including the Minister of Religious Affairs Regulation (PMA) No. 26 of 2019 on Halal Product Assurance Implementation and the Decree of the Head of BPJPH on SJPH Criteria. The findings indicate that the outlet maintains strict halal standards, starting from accepting pre-certified raw materials from the center to the production process, emphasizing the motto